2019
DOI: 10.3390/ijerph16193515
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tobacco Use on Pulmonary Function in Elite Athletes

Abstract: Objective: We sought to investigate the prevalence of smoking and lung function in the large cohort of elite athletes. Methods: This cross-sectional study included 804 athletes competing at international level who were consecutively examined from January to December 2017. Elite athletes were classified in four groups of sport disciplines (skill, power, endurance and mixed): skill (n = 141), power (n = 107), endurance (n = 105) and mixed sport disciplines (n = 451). All participants underwent pre-participation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Numerous studies have proven that there is a relationship between respiratory functions and an athlete's anthropometric indicators, namely athlete's weight and athlete's height [20,21,22]. It is also natural that athletes who are mainly engaged in endurance show changes in indicators of the functional state of the respiratory system, namely adaptive changes in spirometric indicators -FVC, VC inspiratory , FEV1 [15] In the studies of Durmic et al [23] noted the presence of a high correlation dependence of body weight indicators with respiratory function indicators of elite athletes, and the highest was observed between body weight indicators and MVV.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have proven that there is a relationship between respiratory functions and an athlete's anthropometric indicators, namely athlete's weight and athlete's height [20,21,22]. It is also natural that athletes who are mainly engaged in endurance show changes in indicators of the functional state of the respiratory system, namely adaptive changes in spirometric indicators -FVC, VC inspiratory , FEV1 [15] In the studies of Durmic et al [23] noted the presence of a high correlation dependence of body weight indicators with respiratory function indicators of elite athletes, and the highest was observed between body weight indicators and MVV.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the general population, consumption rates of combustible tobacco among elite athletes are lower, most likely because of its detrimental effect on cardiopulmonary capacity [19]. However, there is strong evidence for common use of nicotine among elite athletes, suggesting smokeless tobacco or nicotine replacement therapy as the main route of administration.…”
Section: Nicotinementioning
confidence: 99%
“…However, studies have observed that snus is an oral-consumed and smokeless traditional tobacco, and its use does not affect muscle contractions, fatigue perception, or time to exhaustion [ 7 , 10 ]. Pulmonary function was lower in active smokers than in non-smokers in skill and power sports [ 11 ]. Although Guo et al has indicated that the secretion and production of testosterone might be regulated by the hypothalamic–pituitary–gonadal (HPG) axis through the neuroendocrine system [ 12 ], other report of Peak et al revealed that testosterone had no direct relationship with HPG axis-related hormones [ 13 ].…”
Section: Introductionmentioning
confidence: 99%